IMPACT OF COMPENSATION ON TEAM PERFORMANCE OF STUNTING RISK FAMILY FACILITATORS: MEDIATING ROLE OF JOB SATISFACTION - Abror, Himawan (PT ANTIS INTERNATIONAL PUBLISHER, 2025)
Objective: This study explores the influence of compensation on job satisfaction and team performance within the Family Assistance Team (TPK) framework in Jember Regency, emphasizing job satisfaction as a mediating variable. Method: With 375 sample, data collected through Likert-scale questionnaires and analyzed using Structural Equation Modeling (SEM) based on Partial Least Squares (PLS) via SmartPLS 4. Results: The findings reveal that compensation significantly affects job satisfaction and team performance directly, while job satisfaction mediates the relationship between compensation and team performance. This highlights the critical role of job satisfaction in amplifying the effects of compensation on employee performance. Moreover, the study underscores the necessity of implementing structured compensation systems and satisfaction-monitoring mechanisms to enhance employee performance, particularly in achieving stunting prevention targets. Novelty: While the findings provide actionable insights for policymakers, limitations related to the exploration of contextual factors, such as organizational culture and individual characteristics, suggest avenues for future research to develop a more comprehensive understanding of performance dynamics in similar public health initiatives.